A tale of two cities - Dickens, Charles, 1812-1870.; Maxwell, Richard, 1948-2010. (London, England ; New York, N.Y. : Penguin Books, 2003)
After eighteen years as a political prisoner in the Bastille, the aging Doctor Manette is finally released and reunited with his daughter in England. There the lives of two very different men, Charles Darnay, an exiled French aristocrat, and Sydney Carton, a disreputable but brilliant English lawyer, become enmeshed through their love for Lucie Manette. From the tranquil roads of London, they are drawn against their will to the vengeful, bloodstained streets of Paris at the height of the Reign of Terror, and they soon fall under the lethal shadow of La Guillotine. This edition uses the text as it appeared in its first serial publication in 1859 to convey the full scope of Dickens's vision, and includes the original illustrations by H.K. Browne ('Phiz'). Richard Maxwell's introduction discusses the intricate interweaving of epic drama with personal tragedy.
Introduction -- Dickens chronology -- Timeline -- Further reading -- Note on the text -- Tale of two cities.
Includes updated editorial material, revised Dickens Chronology and new appendix.
Includes bibliographical references (p. xli-xlvii).
Keywords: French fiction -- England -- London; Executions and executioners -- Fiction; Fathers and daughters -- Fiction; Lookalikes -- Fiction; Paris (France) -- History -- 1789-1799 -- Fiction; London (England) -- History -- 18th century -- Fiction; France -- History -- Revolution, 1789-1799 -- Fiction; Historical fiction; War stories